2004
DOI: 10.1007/s00213-004-1895-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of the core and shell subregions of the nucleus accumbens in conditioned cue-induced reinstatement of cocaine seeking in rats

Abstract: The functional integrity of the NACc, but not the NACs, is necessary for conditioned cue-induced reinstatement of cocaine seeking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
187
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 46 publications
28
187
3
2
Order By: Relevance
“…The finding of Di Ciano and Everitt are in agreement with those demonstrating that permanent NAc core lesions had a more pronounced effect than NAc shell lesions on responding reinforced by heroin or cocaine cues in this procedure (Hutcheson et al, 2001;Ito et al, 2004). Fuchs et al (2004) reported that reversible inactivation (muscimol + baclofen injections) of the NAc core, but not the shell, attenuates discrete cue-induced reinstatement of cocaine seeking; the discrete cues were presented contingently during testing. Also potentially relevant here is the finding that reversible inactivation of the dorsomedial prefrontal cortex (tetrodotoxin injections), but not the ventromedial prefrontal cortex, attenuates context-induced reinstatement of cocaine seeking, as measured in a procedure similar to the one used in our study (Fuchs et al, 2005).…”
Section: Role Of the Nac Core And Shell In Drug Seekingsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding of Di Ciano and Everitt are in agreement with those demonstrating that permanent NAc core lesions had a more pronounced effect than NAc shell lesions on responding reinforced by heroin or cocaine cues in this procedure (Hutcheson et al, 2001;Ito et al, 2004). Fuchs et al (2004) reported that reversible inactivation (muscimol + baclofen injections) of the NAc core, but not the shell, attenuates discrete cue-induced reinstatement of cocaine seeking; the discrete cues were presented contingently during testing. Also potentially relevant here is the finding that reversible inactivation of the dorsomedial prefrontal cortex (tetrodotoxin injections), but not the ventromedial prefrontal cortex, attenuates context-induced reinstatement of cocaine seeking, as measured in a procedure similar to the one used in our study (Fuchs et al, 2005).…”
Section: Role Of the Nac Core And Shell In Drug Seekingsupporting
confidence: 85%
“…This anatomical distinction is important because there are reports that NAc core and shell differentially modulate the conditioned and unconditioned behavioral effects of opiate and psychostimulant drugs (Everitt and Wolf, 2002;Di Chiara et al, 2004;Ikemoto and Wise, 2004). For example, reversible or permanent lesions of the NAc core, but not the shell, attenuate cue-controlled cocaine seeking, as measured by the second-order schedule and the cue-induced reinstatement procedures (Fuchs et al, 2004;Ito et al, 2004); see also Di Ciano and Everitt (2001) and Hyytia and Backstrom (2005) for similar findings with ionotropic glutamate receptor antagonists. On the other hand, 6-OHDA lesions of the NAc shell, but not the core, attenuate the reinforcing effects of amphetamine, as measured in the conditioned place preference procedure (Sellings and Clarke, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the present data suggest that mGlu2/3 receptors are involved in regulating the combined effects of nicotine and contextual/discrete stimuli on NAcc shell dopamine in rats. Contextual and discrete stimuli are two distinct entities that can have differential behavioral effects, possibly mediated by different subdivisions (core vs shell) of the NAcc (Chaudhri et al, 2010;Bossert et al, 2007;Fuchs et al, 2004Fuchs et al, , 2008. This study focused on providing a wellsupported conclusion about the conditions that lead to the reversal of nicotine-induced increases in NAcc dopamine levels after the initial surprising lack of reversal of nicotineinduced dopamine increases by LY379268 in Experiment 1.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from analyzing the effects of acute cocaine in the VTA-evoked EPSP-IPSP sequence indicate possible mechanisms underlying the decrease in spontaneous bistability and cortical activity. The acute dose of cocaine used in this study is comparable with the dose of cocaine that a rat will self-administer in a session of 2 h when in an FR1 schedule (average selfadministration ¼ 19.271.4 mg/kg/session, Fuchs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%